0759 Quantification of Neuromuscular Effort in Upper Airways of Pediatric Patients with Obstructive Sleep Apnea. (12th April 2019) - Bates, Alister; McConnell, Keith; Fleck, Robert; Dumoulin, Charles; Woods, Jason; Amin, Raouf
Abstract: Introduction: Airway obstruction in obstructive sleep apnea (OSA) is caused by a breakdown in the balance between neuromuscular control of the airways and aerodynamic forces acting on the airway walls. Computational fluid dynamics (CFD) simulations of respiratory airflow can determine the aerodynamic forces, and realistic airway wall motion can be determined from cine magnetic resonance imaging (MRI). The relationship between these forces and motion reveals the underlying neuromuscular control of the airway. Methods: CFD modeling was performed in three patients with OSA (age=12.2±6.3, obstructive index (OI)=42.1±51.5). CFD simulations modelled airflow during breathing in airway anatomies obtained from MRI and with airway wall motion determined from registration of cine MRI. Respiratory flow rates were recorded synchronously with MRI via an MRI compatible pneumotach. CFD simulations calculated the aerodynamic forces (pressure and wall shear-stress) acting on the airway wall throughout the airway during the breath. Combining these forces with the motion of the airway wall (taking the vector dot product) allowed calculation of the work done by aerodynamic forces on the airway wall and of the neuromuscular work done on the air within the lumen. The total of this effort in the oropharynx and larynx was then calculated over the duration of inhalation and exhalation. Results: The volume of upper airway increased during inhalation and decreased during exhalation, contrary to the air pressure forces. The ratio of aerodynamic to neuromuscular work done in moving the airway wall in the oropharynx and larynx increased with OI, (OI=16.7, 23.5, 101.4 corresponding work ratio=18, 27, 53%). Pressure loss in the same region at peak inhalation also increased with OI (1.5, 19.9, 26.2cmH2 O). Conclusion: In this small cohort of patients, we have demonstrated that neuromuscular control of the airway in relation to the aerodynamic forces acting on the airway is decreased in patients with a high OI. In all cases neuromuscular control of the airway caused more airway motion than aerodynamic forces. Quantification of neuromuscular control in patients with OSA may allow treatment strategies personalized based on the patients' ability to control their airway caliber. Support (If Any)